Switzerland : 2019 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2019)
The Swiss economy has performed relatively well since the global financial crisis. Growth compares favorably with most other advanced countries and aggregate employment has grown robustly. The fiscal position is strong and the external trade surplus remains large and stable despite several episodes of intense appreciation pressure owing to the Swiss franc's reputation as a safe haven. Growth is expected to temporarily dip to 1.1 percent in 2019 on weakness in external demand. Risks to the outlook are tilted down. Switzerland is also facing several policy challenges: low interest rates are fueling risks in the real estate and mortgage markets; persistent subdued inflation has decreased the operational space for monetary policy; and population aging and technological change will require further upskilling and generate new demands for public resources.